CD40L Priming of Platelets via NF‐κB Activation is CD40‐ and TAK1‐Dependent - Kevin Kojok; Souhad El Akoum; Mira Mohsen; Walid Mourad; Yahye Merhi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background CD40 ligand (CD40L) is a thromboinflammatory molecule that predicts cardiovascular events. CD40L is a strong activator of nuclear factor kappa B (NF‐κB) in platelets that primes and enhances platelet activation in response to thrombotic stimuli. In addition to its classical receptor CD40, CD40L binds αIIbβ3, α5β1, and αMβ2 in various cell types. However, the function of the different CD40L receptors on platelets remains unexplored. The present study aims to identify the receptors of CD40L, involved in platelet NF‐κB activation, their downstream signaling and their implication in platelet aggregation. Methods and Results We showed that platelets express CD40, αIIbβ3, and α5β1 and release CD40L in response to sCD40L stimulation. sCD40L alone dose‐dependently induced platelet NF‐κB activation; this effect was absent in CD40−/− mouse platelets and inhibited by the CD40 blockade, but was unaffected by the αIIbβ3 or α5β1 blockade in human platelets. sCD40L/CD40 axis activates transforming growth factor‐β‐activated kinase 1 upstream of NF‐κB. In functional studies, sCD40L alone did not affect platelet aggregation but potentiated the aggregation response in the presence of suboptimal doses of thrombin; this effect was abolished by CD40, transforming growth factor‐β‐activated kinase 1, and NF‐κB inhibitors. Conclusions CD40L primes platelets via signaling pathways involving CD40/transforming growth factor‐β‐activated kinase 1/NF‐κB, which predisposes platelets to enhanced activation and aggregation in response to thrombotic stimuli.